Surgical Treatment for Avulsion Fractures of the Anterolateral Ligament Associated with Periarticular Fractures of the Knee - Wei, Xuelei; Wang, Zengliang; Lu, Yandong; Sun, Jie; Riehl, John (The Journal of Knee Surgery, 2021)
The existence and anatomy of the anterolateral ligament (ALL) of the knee are a somewhat controversial topic in orthopaedic surgery. The fixation of the avulsion fracture of the ALL (Segond fracture), associated with periarticular knee fractures, is rarely given much consideration while the major fracture fragments are reconstructed. This study aims to confirm the existence of ALL and evaluate the clinical outcomes of surgical management for avulsion fractures, involving its insertion, when associated with periarticular knee fractures. Twenty-three patients (16 males and 7 females) with avulsion fractures of the ALL associated with periarticular knee fractures were fixed with a spider plate, cannulated screw, or suture anchor. Eight patients were diagnosed with distal femoral fracture, 10 with tibial plateau fracture, and 5 with tibial eminence avulsion fracture. All patients underwent X-rays at follow-up. Clinical and functional outcomes were assessed with the pivot-shift test, objective and subjective International Knee Documentation Committee (IKDC) score, Lysholm score, and Tegner activity scale. The ALL was found and identified as a distinct ligamentous structure in all patients. Prior to Segond repair, patients had significantly more instability, as determined by pivot-shift test, than seen postoperatively (p < 0.0001). At final follow-up, the mean subjective IKDC score was 83.2 ± 10.3. Fourteen patients were graded A, 6 were graded B, and 3 was graded C on the IKDC objective score. The mean Lysholm score was 85.4 ± 12.2. The mean Tegner score was 7.5 ± 1.2. This study confirmed that the ALL is a distinct structure in the anterolateral portion of the knee. The fixation of the avulsion fracture of the ALL associated with periarticular knee fractures can be an effective procedure without specific complications. Long-term and comparative follow-up studies are necessary to confirm the effects.
Keywords: anterolateral ligament; periarticular knee fractures; avulsion